Diabetic Foot Exercises as an Effective Effort to Reduce Blood Glucose Levels in Diabetes Patients - Wayunah, Wayunah; Kenanga Purbasary, Eleni; Hardianti, Rina; Saefulloh, Muhammad (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Diabetes mellitus (DM) is a global health issue with a rising prevalence. One effective intervention for managing blood glucose levels is diabetic foot exercises, which enhance blood circulation and insulin sensitivity. The purpose of this study is to determine the effect of diabetic foot exercises on blood glucose levels. This study employed a quasi-experimental design with a control group pretest-posttest approach. The sample consisted of 30 respondents divided into intervention and control groups. The intervention group performed diabetic foot exercises twice a week for four weeks. Data were analyzed using the Independent T-test. The intervention group showed a significant decrease in mean blood glucose levels, from 245.40 mg/dL to 204.93 mg/dL, with a difference of 40.47 mg/dL. Conversely, the control group experienced an increase in mean blood glucose levels, from 258.46 mg/dL to 305.80 mg/dL, with a difference of 47.34 mg/dL. Statistical analysis indicated a significant difference between the intervention and control groups, with a p-value of 0.000 (p < 0.05). Diabetic foot exercises effectively lower blood glucose levels in type 2 DM patients. This intervention can serve as an additional therapy for diabetes management, particularly for patients at risk of diabetic neuropathy. Education and widespread implementation of diabetic foot exercises are recommended as an accessible and efficient diabetes control strategy.